Tb3+-sensitized Yb3+ downshifting emission, host-sensitized Yb3+ quantum-cutting emission, Yb3+ sensitized Tb3+ upconversion emissions, and special thermal quenching mechanism in Tb3+/Yb3+-doped NaY(WO4)2 phosphors - Gao, Duan; Liu, Shengyi; Zhang, Xizhen; Zhang, Jinsu; Xu, Sai; Li, Xiangping; Cao, Yongze; Wang, Yichao; Yu, Hongquan; Zhang, Yuhang; Sha, Xuezhu; Wang, Li; et al. (Hanʼguk Seramik Hakhoe chi, 2024)
Tb 3+ –Yb 3+ co-doped NaY(WO 4 ) 2 phosphors with intense near-infrared emission and broad band near-ultraviolet absorption were synthesized by a traditional high‐temperature solid‐state method. The luminescence spectra and fluorescence decays of visible and near-infrared emissions were measured to investigate the luminescence mechanisms. It was found that the energy transfer from Tb 3+ to Yb 3+ cannot result in the quantum-cutting emission but downshifting emission. The luminescence mechanism of the singlet and triplet states (WO 4 ) 2− sensitizing Yb 3+ were explored and ascribed to quantum-cutting. A two-photon process for the green upconversion emission was verified by analyzing the dependence of the upconversion emission intensity on 980 nm laser operating current. On the analyses of the temperature‐dependent emission spectra and temperature‐dependent fluorescence decay curves, it was revealed that the luminescence thermal quenching of Tb 3+ in NaY(WO 4 ) 2 : Tb 3+ /Yb 3+ phosphor is attributed to crossover process within the temperature range of 303–483 K and can be ascribed to both crossover and nonradiative relaxation processes when the temperature is higher than 513 K.